Inducing Persistent Flow Disturbances Accelerates Atherogenesis and Promotes Thin Cap Fibroatheroma Development in D374Y-PCSK9 Hypercholesterolemic Minipigs. Issue 11 (15th September 2015) - Pedrigi, Ryan M.; Poulsen, Christian Bo; Mehta, Vikram V.; Ramsing Holm, Niels; Pareek, Nilesh; Post, Anouk L.; Kilic, Ismail Dogu; Banya, Winston A.S.; Dall'Ara, Gianni; Mattesini, Alessio; Bjørklund, Martin M.; Andersen, Niels P.; et al.
<x xml:space="preserve">Abstract</x> Background— Although disturbed flow is thought to play a central role in the development of advanced coronary atherosclerotic plaques, no causal relationship has been established. We evaluated whether inducing disturbed flow would cause the development of advanced coronary plaques, including thin cap fibroatheroma. Methods and Results— D374Y-PCSK9 hypercholesterolemic minipigs (n=5) were instrumented with an intracoronary shear-modifying stent (SMS). Frequency-domain optical coherence tomography was obtained at baseline, immediately poststent, 19 weeks, and 34 weeks, and used to compute shear stress metrics of disturbed flow. At 34 weeks, plaque type was assessed within serially collected histological sections and coregistered to the distribution of each shear metric. The SMS caused a flow-limiting stenosis, and blood flow exiting the SMS caused regions of increased shear stress on the outer curvature and large regions of low and multidirectional shear stress on the inner curvature of the vessel. As a result, plaque burden was ≈3-fold higher downstream of the SMS than both upstream of the SMS and in the control artery (P<0.001). Advanced plaques were also primarily observed downstream of the SMS, in locations initially exposed to both low (P<0.002) and multidirectional (P<0.002) shear stress. Thin cap fibroatheroma regions demonstrated significantly lower shear stress that persisted over the duration of the study in comparison with other plaque types (P<0.005). Conclusions— These data support a causal role for lowered and multidirectional shear stress in the initiation of advanced coronary atherosclerotic plaques. Persistently lowered shear stress appears to be the principal flow disturbance needed for the formation of thin cap fibroatheroma.